IMMUNOSUPPRESSIVE EFFECT OF HYDROCORTSONE ACETATE DRUG IN THE WORM EXPULSION PROCESS OF THE SWISS ALBINO MICE EXPERIMENTALLY INFECTED WITH NEMATOSPIROIDES DUBIUS LARVAE - NAGARAJALAKSHMI, P.; KUMARI, S. ANITHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Daily doses of Hydrocortisone acetate (HCA) when administered for 10 days to a group of Swiss Albino mice actively immunized for longer duration with 3 spaced doses of 50 + 50 + 100 larvae of Nematospiroides dubius at weekly intervals and for shorter duration with 100 + 100 larvae at weekly intervals exerted significant influence inhibiting the rejection of challenge worm load as evidenced by the retention at various intervals of time. The effect of the drug was more pronounced in mice sensitized for longer duration when compared to shorter duration.